Brief overview on study of genetically modified organisms and assessment of potential risks of their usage for natural species - Yu. Ph. Kartavtsev (A. O. Kovalevsky Institute of Biology of the Southern Seas of RAS, 2021)
Brief information is summarized on the genetically modified organisms (GMOs), methods of their construction, spheres of usage, potential risks of GMOs propagation, necessity, and ranges of control of their usage, inter alia their application to aquatic organisms. The data available allow concluding that the expert community currently has no exact answer concerning the scale of GMOs usage in the country, as well as about the degree of genetic safety of their usage in several fields of industry, especially in semi-closed systems for growing plants and rearing of animals and other living beings in the Russian Federation and other countries. Application of molecular genetic markers and new law regulations will help in monitoring GMOs usage in agriculture and other industries in Russia and responding to requests from the Russian Government and social institutions, as well as many challenges on genetic safety.